Green aqueous surface modification of polypropylene for novel polymer nanocomposites - Thakur, Vijay Kumar; Vennerberg, Danny; Kessler, Michael R. (American Chemical Society, 2014)
Polypropylene is one of the most widely used commercial commodity polymers; among many other applications, it is used for electronic and structural applications. Despite its commercial importance, the hydrophobic nature of polypropylene limits its successful application in some fields, in particular for the preparation of polymer nanocomposites. Here, a facile, plasma-assisted, biomimetic, environmentally friendly method was developed to enhance the interfacial interactions in polymer nanocomposites by modifying the surface of polypropylene. Plasma treated polypropylene was surface-modified with polydopamine (PDA) in an aqueous medium without employing other chemicals. The surface modification strategy used here was based on the easy self-polymerization and strong adhesion characteristics of dopamine (DA) under ambient laboratory conditions. The changes in surface characteristics of polypropylene were investigated using FTIR, TGA, and Raman spectroscopy. Subsequently, the surface modified polypropylene was used as the matrix to prepare SiO2-reinforced polymer nanocomposites. These nanocomposites demonstrated superior properties compared to nanocomposites prepared using pristine polypropylene. This simple, environmentally friendly, green method of modifying polypropylene indicated that polydopamine-functionalized polypropylene is a promising material for various high-performance applications.
Keywords: polypropylene; green aqueous modification; dopamine; nanocomposites